Simple in-house flow-injection capillary electrophoresis with capacitively coupled contactless conductivity method for the determination of colistin - Patcharin Chaisuwan (2018)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. An in-house flow-injection capillary electrophoresis with capacitively coupled contactless conductivity detection method was developed for the direct measurement of colistin in pharmaceutical samples. The flow injection and capillary electrophoresis systems are connected by an acrylic interface. Capillary electrophoresis separation is achieved within 2 min using a background electrolyte solution of 5 mM 2-morpholinoethanesulfonic acid and 5 mM histidine (pH 6). The flow-injection section allows for convenient filling of the capillary and sample introduction without the use of a pressure/vacuum manifold. Capacitively coupled contactless conductivity detection is employed since colistin has no chromophore but is cationic at pH 6. Calibration curve is linear from 20 to 150 mg/L, with a correlation coefficient (r2) of 0.997. The limit of quantitation is 20 mg/L. The developed method provides precision, simplicity, and short analysis time.